Representasi Kekerasan Domestik Dalam Keluarga Pada Film Tarian Terakhir - saputro, fiqi; Setiawati, Titin; Mustiawan, Mustiawan (LPPM Universitas Dharma Andalas, 2025)
This study examines how domestic violence, particularly against children, is portrayed in the film Tarian Terakhir (The Last Dance). This film was chosen because it presents an emotional story that is close to social reality, where violence is often hidden behind the walls of the home. A qualitative approach was used with content analysis to analyze six main scenes that depict physical and psychological violence. The results of the study indicate that violence in the film is not only a dramatic element but also reflects power imbalances within family relationships. This finding is supported by data from SIMFONI-PPA and KPAI in 2024, which show high rates of violence against children. Based on media content theory, the film is understood as a medium that shapes public understanding and critiques the normalization of violence. However, this study has limitations as it only analyzes one film and does not involve the perspectives of victims or experts. Therefore, it is recommended that future research adopt a cross-media and multidisciplinary approach to examine the representation of violence within families more broadly and deeply.